Sacramentalità: la mediazione della Chiesa - Salato, Nicola (Rassegna di teologia, 2017)
Sacramentality is, in ecclesiology, a theme that still does not present a unique consideration and collocation; the approach to it takes place with a broad hermeneutic venture and for these reasons it can not be reduced to a mere category to "say" the Church. The hermeneutic-sacramental category, in fact, has the task of overcoming a fideistic vision of the Church through the creation of a new horizon that consists primarily in its trinitarian and ethical re-enactment, which expresses its complex reality. (English)